Radial artery harvesting with skin bridge technique among patients undergoing coronary artery bypass grafting: an approach for developing countries - Junejo, Sanaullah; Virani, Sehar Salim; Mahmood Khan, Tariq; Ahmed Sami, Shahid (Journal of the Pakistan Medical Association, 2023)
The risk of wound dehiscence and sternal infections remains high after coronary artery bypass grafting, especially in patients with diabetes. Radial artery is a potential alternative which has shown good post-operative outcomes with least complications. Open and endoscopic techniques for harvesting have been used till now. We propose an interrupted or bridging technique, for harvesting the radial artery. This report describes 25 patients undergoing CABG, using radial artery graft, harvested via skin bridge technique, at South City Hospital, Karachi. It in better cosmetic outcome, reduced postoperative pain, shortened hospital stays and increased level of satisfaction. The interrupted technique offers less invasive cost-effective approach compared to open and endoscopic techniques for radial artery harvesting. Key words: Coronary artery bypass grafting, Radial artery harvesting, Arterial revascularisation.